Analysis of Geographical Phenomena of Snowstorms in Japan - Raza, Hassan (Prevention and Treatment of Natural Disasters, 2023)
Snowstorms are among the most significant natural phenomena affecting Japan, shaped by the country’s unique geographical location, climatic diversity, and mountainous terrain. This paper provides a comprehensive analysis of the geographical phenomena underlying snowstorms in Japan, examining their causes, patterns, and impacts. The interplay of Siberian air masses, ocean currents, and the Japanese Alps results in some of the heaviest snowfalls globally, particularly along the Sea of Japan coastline. These snowstorms impact transportation, infrastructure, economy, human safety, and the environment, creating both challenges and opportunities for the nation. The study explores Japan’s advanced adaptation and mitigation strategies, including snow-resistant infrastructure, effective governance, community resilience, and cutting-edge weather prediction systems. Furthermore, it addresses the influence of climate change on snowstorm patterns and highlights the need for climate-resilient infrastructure and global collaboration in managing these extreme weather events. By shedding light on the dual nature of snowstorms—both as a disruptive force and a resource, this paper underscores the importance of sustainable and innovative approaches to snowstorm management in Japan and other snow-prone regions worldwide.